A COMPARATIVE STUDY OF ANESTHETIC BLOCK TECHNIQUES (V-BLOCK VS. H-BLOCK) FOR REMOVAL OF INGROWN TOENAIL - FAROOQI, A; ZAHEER, F; SALMAN, S; SADIA, .; SHAIKH, SN; RIMSHA, S (Biological and Clinical Sciences Research Journal, 2024)
Ingrown toenail (onychocryptosis) is a common and painful condition often requiring surgical intervention. Adequate local anaesthesia is crucial for patient comfort and surgical success. However, the optimal anaesthetic technique for this procedure remains debated. Objectives: This study aimed to evaluate and compare the anaesthetic efficacy, patient comfort, onset and duration of anaesthesia, and occurrence of complications between the V-block and H-block techniques during surgical procedures for ingrown toenail removal. Methods: After ethical approval, an open-label randomised control trial was conducted at Ruth PFAU Civil Hospital, Dow University of Health Sciences, Karachi. One hundred eighty-eight patients, aged 18 and above, with type II, III, and IV onychocryptosis were included. Patients were randomly assigned to either Group A (H-technique, n=94) or Group B (V-technique, n=94). Local anaesthesia was administered using 5 ml of 2% Xylocaine diluted in 5 ml of distilled water. Pain severity, numbness, and loss of sensation were assessed at 2, 5, and 10 minutes post-injection. Data were analysed using SPSS version 26. Results: Group A (H-technique) had a significantly younger average age (35.12±9.8 years) compared to Group B (39.77±13.01 years). Gender distribution differed significantly, but weight did not. At 2 minutes, Group B reported more pain (90% vs. 86.5%, P=0.045). At 5 and 10 minutes, Group B showed higher numbness and loss of sensation, indicating more comprehensive anaesthesia. Efficacy at 10 minutes was higher in Group B (44% vs. 39%, P=0.045), with similar trends at 20 minutes but no significant difference. Conclusion: The V-block technique offers rapid onset and effective pain relief for routine procedures, while the H-block technique provides more comprehensive and sustained anaesthesia for complex surgeries. The selection of anaesthetic techniques should be based on the surgical context to optimise patient outcomes. Further research is recommended to enhance these techniques' efficacy and minimise complications.